Sustainability and Entrepreneurial Intention: Study with Undergraduate Administration Students of Universidade do Oeste de Santa Catarina (Unoesc) - Silveira, Amélia (2018)
This study is about the individual sustainable orientation and the entrepreneurial behavior focused on the Social Entrepreneurial Intention (SEI) and the Entrepreneurial Intention (EI) in the context of a higher education institution of the Western Santa Catarina, Brazil. It was sought to answer the following question: To what extent do the students present social view, social entrepreneurial intention, and entrepreneurial intention? The methodological design was descriptive. For the data collection, a structured questionnaire was applied using the 7-point Likert scale. 70 undergraduate Administration students of Universidade do Oeste de Santa Catarina (Unoesc), Chapecó, answered this questionnaire in 2017. The sample was intentional, convenience, no probabilistic and by accessibility. The results showed that the sustainable entrepreneurship is under development in administration literature. It was possible to confirm that the students have social view, social entrepreneurial intention, and entrepreneurial intention with medium agreement.